Leveraging Spousal Support to Improve Health Promotion in Serious Mental Illness: A Case Study. (April 2017) - Renn, Brenna N.; Thakur, Aishwarya; Trahan, Lisa H.; Stanley, Melinda A.; Dubbert, Patricia; Evans-Hudnall, Gina
Although the majority of Veterans are overweight or obese, and many have comorbid mental health disorders, little is known about the most effective way to intervene in this complex population. This case describes a telephone-based cognitive-behavioral treatment for depression and weight management with an obese Veteran with bipolar disorder. His wife joined sessions to leverage spousal support. The Veteran evidenced variable levels of physical activity and mood fluctuations during treatment; although he reported some degree of positive behavior change and improved social support, he did not lose weight. He continued to endorse moderate levels of depressive symptomatology at the end of the nine-session intervention. This case illustrates the complexity of treating those with chronic serious mental illness and multimorbidities. Further research is needed to inform interventions that concurrently improve mental health symptomatology and weight-related outcomes in chronic, complex cases.